The communication in Latin American code - Torrico Villanueva, Erick (2016)
In pointing out Latin America as a distinct locus of enunciation for Communication it is not intended to materialize a kind of epistemological privilege for this territory. It is to explore and exploit the fact that the region synthesizes a structural placement from which it is possible to carry out a non-Eurocentric reinterpretation of the history of the world, and promoting the dismantling of the mechanisms of compulsory westernization to which the world surrendered after the integration of America to planetary geography. Feasible, therefore, from this part of the globe to raise a new alter(n)ative communication, first in the epistemological-theoretical level and then the praxis.